Tick population dynamics in the city of Košice (Eastern Slovakia): a public health study - Hajdová, Blažena; Cellengová, Zuzana; Peťko, Branislav; Ondrejková, Anna; Lipinský, Jakub; Drážovská, Monika (Frontiers in Ecology and Evolution, 2024)
IntroductionUrban habitats, including green spaces, host diverse ecosystems where ticks and their hosts thrive, posing public health risks. Understanding the presence of ticks in urban areas is crucial for the effective management of those parasites.MethodsA three-year study (2021 - 2023) on the presence of ticks in urban green spaces was conducted in the city of Košice, Slovakia. A total of 3443 ticks were collected in woodland and scrubby vegetation areas located in the town by applying the flagging methods.ResultsThree different species of ticks – Ixodes ricinus, Dermacentor reticulatus, and Dermacentor marginatus, were found in the urban spaces, while I. ricinus was the most prevalent tick species (64.7%), followed by D. reticulatus (35.2%). Dermacentor reticulatus, typically found in rural habitats, was detected right in the city centre, where its typical habitat is absent. Significant differences in tick abundance were observed between the scrubby areas (55.9%) and the woodland areas (44.5%), with D. reticulatus being predominantly found in the former. Monthly tick density varied across years, with D. reticulatus activity starting early in February.DiscussionThe findings of the study highlight the importance of considering geographical and ecological factors in tick distribution studies, especially in urban settings. Effective public health management strategies should incorporate efforts aimed at understanding the presence and behaviour of ticks in urban environments, emphasising the need for monitoring those species and taking necessary measures, such as vegetation maintenance, in order to mitigate the tick-related risks in urban areas.